Mosaic RBD nanoparticles protect against challenge by diverse sarbecoviruses in animal models - Cohen, Alexander A.; van Doremalen, Neeltje; Greaney, Allison J.; Andersen, Hanne; Sharma, Ankur; Starr, Tyler N.; Keeffe, Jennifer R.; Fan, Chengcheng; Schulz, Jonathan E.; Gnanapragasam, Priyanthi N. P.; Kakutani, Leesa M.; West, Anthony P.; et al. (Science (American Association for the Advancement of Science), 2022)
To combat future severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants and spillovers of SARS-like betacoronaviruses (sarbecoviruses) threatening global health, we designed mosaic nanoparticles that present randomly arranged sarbecovirus spike receptor-binding domains (RBDs) to elicit antibodies against epitopes that are conserved and relatively occluded rather than variable, immunodominant, and exposed. We compared immune responses elicited by mosaic-8 (SARS-CoV-2 and seven animal sarbecoviruses) and homotypic (only SARS-CoV-2) RBD nanoparticles in mice and macaques and observed stronger responses elicited by mosaic-8 to mismatched (not on nanoparticles) strains, including SARS-CoV and animal sarbecoviruses. Mosaic-8 immunization showed equivalent neutralization of SARS-CoV-2 variants, including Omicrons, and protected from SARS-CoV-2 and SARS-CoV challenges, whereas homotypic SARS-CoV-2 immunization protected only from SARS-CoV-2 challenge. Epitope mapping demonstrated increased targeting of conserved epitopes after mosaic-8 immunization. Together, these results suggest that mosaic-8 RBD nanoparticles could protect against SARS-CoV-2 variants and future sarbecovirus spillovers. The COVID-19 pandemic has been ongoing for more than 2 years now, and new variants such as Omicron are less susceptible to the vaccines developed against earlier lineages of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In addition, there is continued risk of spillovers of other animal sarbecoviruses into humans. There is thus a need for vaccines that will give broader protection. Cohen et al . developed mosaic nanoparticles that display the receptor-binding domains (RBDs) from SARS-CoV-2 and seven other animal sarbecoviruses. Mosaic nanoparticles protected against both SARS-CoV-2 and SARS-CoV challenges in animal models even though the SARS-CoV RBD was not present on the mosaic-8 RBD nanoparticles. By contrast, a homotypic SARS-CoV-2 RBD nanoparticle (presenting only SARS-CoV-2 RBDs) only protected against a SARS-CoV-2 challenge. —VV A mosaic sarbecovirus nanoparticle protects against SARS-2 and SARS-1, whereas a SARS-2 nanoparticle only protects against SARS-2.